Le débat sur les notions de dissuasion et de sécurité - Jervis, Robert (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1989)
This article deals with two general arguments about how nuclear weapons might produce or prevent war, both based on themes present in pre-nuclear eras. The first debate is over whether traditional military policies increase or decrease the likelihood of war, whether a policy relying on implicit or explicit threats deter or provoke. The second debate centers on how nuclear weapons are brought into the framework of force and threats, and how deterrence can be mode most effective, through a posture of deterrence by denial versus deterrence by punishment. Involved in these arguments are disputes over international politics, the nature and intentions of the Soviet Union, and the changes brought about by nuclear weapons.